Assessment of workplace product accessibility: a human factors perspective. - Fain WB (Work, 2006)
This paper illustrates the advantages of using human factors evaluation techniques as a method of informing rehabilitation service provider decisions about client care and assistive technology selection. Successful integration of accessibility evaluation techniques can strengthen an evidence based service program and offer service providers another tool for providing efficient, effective, and rapid services to individuals in need. With accessibility evaluation data showing the functional abilities required to operate a given product or set of products, it is possible to empirically demonstrate that an individual has the potential to successfully utilize the provided workplace equipment. Conversely, if the accessibility evaluation data reveal that the functional capabilities required to use a product exceed the capabilities of a given user, it would be possible to demonstrate the need for particular interventions or accommodations. With accessibility evaluation data, service providers can make better informed decisions about client care.